Sectorial evaluation and characterization of internal marketing orientation through multicriteria analysis - Muñoz-Martos, María del Mar; Kazakov, Sergey; Ruiz-Alba Robledo, José Luis (Springer, 2024)
This research carries out a comparative analysis of the Internal Market Orientation (IMO) to a sample of small and medium enterprise companies, which has been divided into nine groups based on their business sectors. Applying the statistical technique of structural equations, the coefficients of four IMO inputs in each busi- ness sector are obtained. Next, the PROMETHEE multicriteria technique is applied to obtain a composite indicator of the IMO implementation of each business sector. The value of the composite indicator together with the GAIA plane allow to dis- tinguish the differences of the IMO profiles, their strengths and their weaknesses. The results show the divergences in the IMO inputs according to the sector, which is evidence that the business sector is a predictor of the IMO implementation of a company.
Keywords: Mercado - Investigación; Mercado - Análisis; Internal Market Orientation; Sectorial evaluation; Composite indicator; PROMETHEE; GAIA plane